The economics of organized crime in Europe - Roškot, Martin (2017)
This thesis was conducted to investigate the cyber area of organized crime - cyber-crime, as it represents a potential growing threat to public and private organisations. The ongoing development of the internet and creation of new opportunities for doing business internationally through e-commerce makes more businesses operating in the cyber space vulnerable to cyber-attacks. This thesis investigates the impact of ransomware cyber-attacks “WannaCry” and “Petya” on stock prices of publicly traded companies in the EU. This dissertation also analyses a set of case studies related to largest recent cyber-crime events which happened in the first half of 2017. The goal of this thesis is to address these questions:1. Is the cyber-crime a threat to companies?2. How does cyber-crime announcements and publications affect stock prices?